Modern public pealth problems and solutions: An undergraduate capstone course to prepare the next generation of public health practitioners to enhance health equity - Minlikeeva, Albina N.; Amato, Katharine A.; Przybyla, Sarahmona M. (Frontiers in Public Health, 2022)
With a growing emphasis on health equity in public health practice and research, ensuring a competent and skilled public health workforce is critical to advancing the public health mission of a healthier nation. The expansion of undergraduate public health programs provides a unique opportunity for more extensive training and education of the next generation of public health professionals and to center undergraduate public health education around the need to be competent in addressing health disparities to achieve health equity. Following national accreditation standards set by the Council on Education for Public Health (CEPH), undergraduate Bachelor of Public Health (BSPH) students at the University at Buffalo (UB) must complete a capstone course before graduation. This course focuses on integrating and synthesizing knowledge acquired from the BSPH core curriculum through analysis, explanation, and addressing public health problems via an interdisciplinary approach. We designed the most recent iterations of the capstone class based on the model that includes cross-cutting skills as defined by CEPH, evidence-based decision-making skills, established learning objectives of the course, and centering on health equity. This course also builds on the students' previously acquired knowledge with an ultimate goal to prepare the graduating seniors for the “real world” health equity-related public health activities. As a part of the coursework, students complete case studies, article reviews, and active learning group activities that target each component of the model. The final products of the course are a synthesis paper and oral presentation based on a public health problem as identified through surveillance data, analyzing causes of this problem, identifying critical stakeholders, creating an evidence-based solution to the problem, and explaining how health inequities may be addressed through the proposed solution. Centering the culminating course for BSPH undergraduate students on health equity will help ensure a competent and skilled workforce, informed by accreditation standards and prepared to lead our national public health goal of improved and equitable population health.